2014
DOI: 10.1111/are.12577
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary substitution of sea tangle (ST),Laminaria japonicawith rice bran (RB) on growth and body composition of juvenile abalone (Haliotis discus)

Abstract: Dietary substitution effect of sea tangle (ST) with rice bran (RB) on growth and carcass composition of juvenile abalone (Haliotis discus) was determined. Juvenile abalone was acclimated to the experimental conditions for 4 weeks. Seventy juvenile abalone averaging 0.43 g were randomly distributed into each of the 18, 70 L plastic rectangular containers. The experimental diets were fed to abalone once a day at a satiation level with a little leftover. The feeding trial lasted for 16 weeks. Survival of abalone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
(34 reference statements)
5
19
3
Order By: Relevance
“…Unlike Kim et al (2015)'s study, 50% and 100% substitution of MA with rice b ran in the FM 50+MA50 and FM50+MA 100 diets, respectively, produced poorer weight gain of abalone compared to the Std and FM50 d iets in this study. The differences could have resulted from those in MA used in both studies.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…Unlike Kim et al (2015)'s study, 50% and 100% substitution of MA with rice b ran in the FM 50+MA50 and FM50+MA 100 diets, respectively, produced poorer weight gain of abalone compared to the Std and FM50 d iets in this study. The differences could have resulted from those in MA used in both studies.…”
Section: Discussioncontrasting
confidence: 91%
“…Abalone are known to be herbivorous and feed mostly on MA, which is usually low in protein and lipid, but high in carbohydrate, 400-500 g/kg in the wild (Thongrod, Tamt in, Chairat, & Boonyaratpalin, 2003). Unlike this study, however, Kim et al (2015) reported that 400 g/kg substitution of L. japonica with rice bran at 200 g/kg in the diet achieved the best specific gro wth rate of abalone, H. discus and concluded that 100% substitution of L. japonica with rice bran at 200 g/kg in the diet was successfully made without retardation (Reyes & Fermin, 2003). Biological criteria of abalone measured in this study (shell length, shell width, shell height and soft body weight), except for the ratio of the soft body weight to total weight seemed to be closely related to growth rate of abalone.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations